1997
DOI: 10.1029/96jd03651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition variations in cloud droplet populations on aqueous‐phase chemistry

Abstract: Abstract. We prove that the use of a cloud or fog droplet population's volume weighted average pH results in the underestimation of the actual rate of sulfate production for most atmospheric conditions. To quantify the magnitude of this error, we have developed two aqueous-phase chemistry models: a droplet size-resolved model and a bulk chemistry model. The discrepancy between the results of these two models indicates the magnitude of the error introduced by using bulk aqueous-phase properties. This error depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…The rate of the reaction SO 2 + O 3 → SO 4 is controlled by the pH of cloud water (Gurciullo and Pandis, 1997;Kreidenweis et al, 2003) and has been identified as an important uncertainty in the global sulfur cycle (Faloona, 2009). We assume this reaction occurs in low-level clouds (Fig.…”
Section: Activation Diameter (P4)mentioning
confidence: 99%
“…The rate of the reaction SO 2 + O 3 → SO 4 is controlled by the pH of cloud water (Gurciullo and Pandis, 1997;Kreidenweis et al, 2003) and has been identified as an important uncertainty in the global sulfur cycle (Faloona, 2009). We assume this reaction occurs in low-level clouds (Fig.…”
Section: Activation Diameter (P4)mentioning
confidence: 99%
“…These results suggest different formation pathways for sulfate and nitrate. Particle-phase sulfate resulted predominantly from sulfur dioxide oxidation in the cloud free atmosphere (Tyndall and Ravishankara, 1991) and, more commonly, SO 2 conversion in clouds and fogs (Gurciullo and Pandis, 1997;Zhang et al, 1999). The preferential enrichment of nitrate in inorganic ions-rich particles was evidence of a predominant gas-phase source for nitric acid and precursors, followed by partitioning and heterogeneous/aqueous chemistry.…”
Section: Mixing State Of Biomass Burning Particles With Secondary Spementioning
confidence: 99%
“…The microphysics of cloud and fog droplets affects the chemical composition of the droplets as a function of their size. 73,74 Consequently, it may be necessary to add some treatment of the droplet size distribution in the 3-D PM models that currently assume that all droplets have the same chemical composition.…”
Section: Aqueous-phase Chemistrymentioning
confidence: 99%